First Record of Myxosporean Parasites in the Gills of Flathead Mullet (Mugil cephalus : Mugilidae) in Lattakia Coasts. - Salman, Hassan; Dayoub, Amal; Kurhaily, Nasreen (Latakia University Journal -Biological Sciences Series, 2018)
Four different Myxosporean fish parasites belonging to the genus Myxobolus: (M. muelleri; M. parvus; M. bizerti and M. ichkeulensis) were recorded. They were found in gills of flathead mullet (Mugil cephalus) collected from three different areas of Lattakia coasts: Marine researches, Lattakia port, Al-Kabir Al-Shimali River Estuary, between March 2014 and February 2016. فإrom the SyriTan costesrdedFebruary 2016rine researches , Alkabir Alshimali river estuary captured from hese species were recorded for the first time in the Syrian coast in this study. The prevalence of infection was 15.61% at Lattakia port region, 10.95% at Al-kabir Al-Shimali River Estuary and 10.23% at the marine researches region. The highest prevalence (10.59%) was recorded by M. muelleri, while the lowest one (7%) was recorded by M. parvus. These four species occurred in all seasons, the highest distribution was recorded in summer (44.29%) and spring (42.75%). أول تسجيل لطفيليات البوغيات المخاطية (Myxosporean) ضمن غلاصم أسماك البوري أفطس Mugil cephalus (Mugilidae) في شواطئ اللاذقية تم تسجيل أربعة أنواع مختلفة من طفيليات البوغيات المخاطية Myxosporean التابعة لجنس Myxobolus وهي (M. muelleri; M. parvus; M. bizerti and M. ichkeulensis), وجدت في غلاصم أسماك البوري أفطس (Mugil cephalus) التي تم اعتيانها من ثلاث مناطق من شواطئ اللاذقية : المعهد العالي للبحوث البحرية ومرفأ اللاذقية ومصب نهر الكبير الشمالي, في الفترة الممتدة بين آذار2014 وشباط 2016. سجلت هذه الأنواع الأربعة لأول مرة في الساحل السوري في هذه الدراسة. بلغت نسبة الخمج 15.61% في منطقة مرفأ اللاذقية, و 10.95% في منطقة مصب نهر الكبير الشمالي, و 10.23% في منطقة البحوث البحرية. سجل النوع M. muelleri أعلى نسبة خمج حيث بلغت 10.59%, بينما سجل النوع M. parvus. أدنى نسبة خمج بلغت 7% فقط. ظهرت هذه الأنواع الأربعة في كافة فصول السنة وسجل الانتشار الأكبر لها في فصل الصيف بنسبة 44.29% والربيع بنسبة 42.75%.